Implementation of UNSC DPRK Sanctions Regime in South Asia - Lt. Col. Zawar Haider Abidi (Retd) (CISS Insight Journal, 2022)
Nuclear program of Democratic People’s Republic of Korea (DPRK) has been of considerable concern for the international community since its initiation in 1962. In 2006, the United Nations Security Council adopted nine major sanctions resolutions on North Korea after its nuclear test on 9 October, 2006. Each resolution condemned DPRK’s nuclear and ballistic missile activity. It called upon North Korea to cease its illicit activities which are in violation of previous UN Security Council resolutions. In addition to imposing sanctions, the resolutions gave UN member states the authority to interdict and inspect North Korean cargo within their territorial waters, and seize illicit shipments. The sanctions regime was amended and extended by later UNSC resolutions, in response to subsequent nuclear and missiles tests by DPRK. With regards to its implementation by South Asian states, the 1718 committee with its panel of experts reported that a number of South Asian states including Afghanistan, Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan and Sri Lanka have been violating the provisions of the DPRK sanction regime and demanded from them to submit their national reports.